Advanced Nonplatinum Oxygen Reduction Electrocatalysts Prepared by Low‐Temperature Plasma Technology. Issue 12 (7th October 2022) - Qin, Chu; Hu, Ting-Ting; Tian, Shijun; Jiang, Zhong-Jie; Jiang, Zhongqing
Abstract : With the continuous development of technology and the increasing energy demand, it is necessary to develop new energy‐storage and conversion devices. Oxygen reduction reaction (ORR) is a key step in energy‐conversion processes and the synthesis of new materials for highly efficient ORR electrocatalyst is critical in solving the energy problems. To enhance the activity of the electrocatalysts and expose more active sites on the surface, plasma technology is utilized to modify the catalyst surface through etching, heteroatom doping, and surface functionalization. Low‐temperature plasma technology is now used extensively in the synthesis and modification of materials. With the advantages of being highly efficient, environment friendly, and affordable, the low‐temperature plasma technology holds great potential for development in the future. Herein, the synthesis and modification of nonplatinum ORR catalysts using new advances in low‐temperature plasma technology are summarized. The application and development potential of plasma surface treatment and plasma synthesis on nonplatinum ORR catalysts are discussed to provide perspectives for future research in this field. Abstract : Plasma treatment is a more promising approach for surface modification and material synthesis than chemical methods due to its shorter reaction time, high efficiency, nonpolluting processing, etc. Progress, types, and challenges of nonplatinum oxygen reduction electrocatalysts prepared by low temperature plasma technology are critically evaluated.